Optimal path planning algorithms in virtual environments [electronic resource] - Rohayanti Hassan, 1980- 509858 (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2006